A checklist of the Iranian Mordellidae (Coleoptera: Tenebrionoidea) - Ruzzier, Enrico; Ghahari, Hassan; Horák, Jan (Zootaxa, 2017)
The Mordellidae Latreille, 1802 (Coleoptera: Tenebrionoidea) fauna of Iran is summarized. A total of 48 species are reported, subdivided into ten genera: Dellamora Normand, Mediimorda Méquignon, Mordella Linnaeus, Mordellaria Ermisch, Mordellistena A. Costa, Mordellistenula Stchegoleva-Barovskaya, Mordellochroa Emery, Paratomoxioda Ermisch, Stenalia Mulsant, and Variimorda Méquignon. Mordellistena (Mordellistena) batteni Horák, 1980, Mordellistena (Mordellistena) humeropicta Ermisch, 1963, Mordellistena (Mordellistena) intersecta Emery, 1876, Mordellistena (Mordellistena) neuwaldeggiana (Panzer, 1796), Mordellistena (Mordellistena) parabrevicauda Ermisch, 1965, Mordellochroa abdominalis (Fabricius, 1775), Stenalia escherichi Schilsky, 1899 and Stenalia gracilicornis Baudi de Selve, 1878 are new country records and the new taxonomic combination is proposed Mediimorda fallaciosa (Stshegoleva-Barowskaja, 1930) n. comb.